Pendampingan Pembuatan Alat Peraga Edukatif Untuk Media Pembelajaran Guru SD - Novi Purwaningsih; Nanik Setyowati (Social Science Academic, 2023)
The article discussed the process of rendering educational (ape) infant (grade 1) AIDS to an abcd approach. The main focus of this article is the process of referring-phase taken at secondary school, pomahan village, pomahan district. As a companion, researchers conducted the identification of the obstacles and needs faced by elementary pomahan. The method used is the abcd method for which this approach is based on the assets, strength and potential found in ll pomahan primary school. The goal of this chaperone is to help class 1 teacher teacher especially to make it easier to teach and to teach well and qualified according to the needs of the education unit. Literacy fundamentals as life skills of them are read-write literacy and numerical literacy. This capability needs to be developed since early childhood.It is hoped that in the implementation of the introduction of literacy, teachers of early childhood education capable of designing in accordance with the peculiarities of their experiences in the education of their children. Teachers required to be creative in making education toys as the tools to introduce literacy. Activities devotion is intended to give assistance in the context of assisting teachers in improving creativity in the manufacture of APE for the introduction of literacy. Three strategies in devotion to conducting, the implementation of devotion in theoretical strategy, practice, and assisted by each. The result of this chaperone is that teachers can make educational (ape) displays of alphabets that can be used to develop the child's introduction and understanding of letters of the alphabet. The conclusion of this introduction is to know and understand the letters of the alphabet receive a very positive response from the teacher, ape knowing and understanding the letters of the alphabet is done together and participants can follow them carefully